2013
DOI: 10.1177/0734242x13492840
|View full text |Cite
|
Sign up to set email alerts
|

Leachate risk and identification of accumulated heavy metals in Pangasius sutchi

Abstract: Pollutants put great stress on the environment, especially the aquatic ecosystem; therefore, the ease with which pollutants migrate in water is a subject of global concern. In this study, leachate from landfill that was analyzed with the objective of understanding the potential impact to the environment was tested on Pangasius sutchi. Heavy metals available at various concentrations in raw leachate samples of both closed and active landfills necessitated the determination of their degree of bioaccumulation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…Zhang et al (2013) found for the landfills X, S and N that the concentrations of Zn were 17.21, 532.5 and 1,331.25 mg L −1 , respectively. In a young leachate (BOD/COD = 0.5) from a sanitary landfill, the concentrations of Zn, Cr and Fe were 827 mg L −1 , 25.7 mg L −1 and 97.7 mg L −1 respectively (Fauziah et al, 2013). Cobalt (Co) showed an intense leaching in the methanogenic phase (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Zhang et al (2013) found for the landfills X, S and N that the concentrations of Zn were 17.21, 532.5 and 1,331.25 mg L −1 , respectively. In a young leachate (BOD/COD = 0.5) from a sanitary landfill, the concentrations of Zn, Cr and Fe were 827 mg L −1 , 25.7 mg L −1 and 97.7 mg L −1 respectively (Fauziah et al, 2013). Cobalt (Co) showed an intense leaching in the methanogenic phase (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Landfill leachate may include organic compounds such as benzene, toluene and phenol (Emenike et al, 2012;Aziz et al, 2010;Kulikowska and Klimiuk, 2008), mineral compounds such as Ca, Fe, Mn and Mg (Tatsi and Zouboulis, 2002) and Ag, As, Cd, Cr, Cu, Hg, Ni, Pb and Zn (Mojiri et al, 2016;Gajski et al, 2012;Budi et al, 2016;Brennan et al, 2015;Amor et al, 2015;Hilles et al, 2015;Fauziah et al, 2013;Khattabi et al, 2002). Some of these metals are in a concentration higher than 1.0 mg L −1 (trace metals).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cavarozzi, 1988;P. M. Cavarozzi, 1991;Garretón, 1997;O'Donnel, Schmitter, & Whitehead, 1994;Sader, 2001) A democracia brasileira renasceu não a imagem e semelhança da campanha pelas eleições diretas, senão a imagem e semelhança do pacto de elite no colégio eleitoral 14 , o que significava que nascia marcada pela fusão entre o novo e o velho" (Sader, 2001). Sader (2001) sublinha ainda que, no caso brasileiro, as estruturas econômicas se mantiveram, basicamente, as mesmas depois da mudança do regime.…”
Section: Conclusãounclassified
“…Leachate is the liquid/fluid that flows out from waste because of increased moisture levels from water penetration or degradation. The global characterization of leachate, especially from municipal solid waste (MSW) landfills, has shown that it is highly heterogeneous and often contains massive amounts of dissolved organic matter, pesticides, xenobiotics, and heavy metals (Emenike et al, , 2012Fauziah et al, 2013;Kjeldsen et al, 2002). When any landfill lacks proper liners and an adequate collection system for the leachate generated from waste degradation, raw leachate will laterally seep into soil compartments and contaminate the soil.…”
Section: Introductionmentioning
confidence: 99%